2015
DOI: 10.1111/ncn3.12026
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo‐controlled trial of zonisamide in patients with Parkinson's disease

Abstract: Background: We previously showed that zonisamide significantly improved parkinsonian symptoms by a multicenter, double-blind clinical trial. Aim: To confirm the efficacy of zonisamide on Parkinson's disease, a phase 3, randomized, placebo-controlled, multicenter, double-blind trial was carried out in Japan. Methods: Participants had advanced Parkinson's disease taking L-dopa with at least one other antiparkinson drug, but were developing a deterioration of response to L-dopa therapy. The trial consisted of a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…The effect size of zonisamide 50 mg/d for DLB parkinsonism observed in this study was similar to that for PD parkinsonism. 3 5 …”
Section: Discussionmentioning
confidence: 99%
“…The effect size of zonisamide 50 mg/d for DLB parkinsonism observed in this study was similar to that for PD parkinsonism. 3 5 …”
Section: Discussionmentioning
confidence: 99%
“…However, its use has been tempered by concerns about the exacerbation of neuropsychiatric symptoms, including delirium and BPSD, suggesting that doses should be carefully titrated, taking into account the therapeutic benefits versus the possibility of adverse events (AEs) [3][4][5][6]. Zonisamide has been available in Japan for the treatment of parkinsonism since 2009 following clinical trials demonstrating that it improved motor dysfunction and wearing-off in patients with PD, without worsening dyskinesia and psychiatric symptoms such as https://doi.org/10.1016/j.parkreldis.2019.12.005 Received 21 November 2018; Received in revised form 1 October 2019; Accepted 7 December 2019 hallucinations [7][8][9]. Although the pharmacological mechanisms underlying the antiparkinsonian effects of zonisamide remain unclear, dopaminergic (activation of dopamine synthesis and release [10], and inhibition of monoamine oxidase-B [11]) and nondopaminergic (blockade of sodium channels [12] and T-type calcium channels [13,14]) pathways appear to be implicated, in addition to gammaaminobutyric acid (GABA)-ergic transmission via striatal opioid δ1-receptor-associated interaction pathways [15].…”
Section: Introductionmentioning
confidence: 99%
“…Drug repositioning or repurposing is a strategy to discover new efficacies of drugs currently applicable to patients, and may significantly diminish the cost and time for developing drugs as compared with conventional approaches (Padhy and Gupta 2011). Zonisamide, a benzisoxazole derivative, was initially developed as an anti-epileptic drug (Jain 2000), and has been successfully repositioned for Parkinson's disease (Murata et al 2015;Murata et al 2016). Yagi et al (2015) found that zonisamide promoted neurite outgrowth from cultured motor neurons and facilitated axonal regeneration after sciatic nerve injury in mice.…”
Section: Introductionmentioning
confidence: 99%